Development of an Integrated Information System for Community Population Administration Services - Yoana Nabilah Putri; Mushfi Abdulloh Kafa; Muhammad Evan Maulana; Dzikri Ahmad Fauzi; Yusadiningrat Muhammad Dinar; Bambang Irawan (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
The demand for transparent and responsive public services drives the adoption of information technology in government administration processes. This research aims to develop a web-based public complaints information system that allows citizens to report environmental issues directly to relevant agencies. The system was designed using a prototype approach involving user needs analysis, interface design, and functionality testing through black box methods and limited trials (beta testing). Key features include real-time report status tracking, a public monitoring dashboard, and citizen service ratings. Test results showed that all features functioned as designed and received positive feedback from users, with an average satisfaction score of 4.5 out of 5. These findings indicate that the system is able to increase citizen participation, strengthen agency accountability, and facilitate inter-agency coordination. The development of a community-centered system is considered effective in promoting transparency in public services and expanding the adoption of e-Government systems at the local level.